Space and time distribution, and biecology of the croaker, Stellifer brasiliensis ( Teleostei : Sciaenidae ), In the Santos Bay, São Paulo, Brazil - Gianinni, Roberto; Paiva Filho, Alfredo Martins (Arquivos de Ciências do Mar, 2018)
Monthly beach seine hauls and bottom trawls were made in the complex bay-estuary of Santos and São Vicente (lat. 24ºS), between March, 1985 and May, 1986, collection 1,291 specimens of the croaker, Stellifer brasiliensis. This study analyses species characteristics such as occurrence, abundance, length distribution, weight/length relationship, growth, recruitment and mortality, and influence of environmental factors on the species distribution. S. brasiliensis occurred all year round in bottom trawls, being more abundant between December and May ( summerfall ), in deeper water areas with high salinity and dissolved oxygen contents, and low temperature, when the young of the year wre first caught. The annual recruiment pattern showed two not-well defined pulses, and the high rates of mortality and exploitation suggest the occurrence of overfishing by the used fishing gear.